Exploring the breeding diet of the Black Sparrowhawk (Accipiter Melanoleucus) on the Cape Peninsula - Baigrie, Bruce (Department of Biological Sciences, 2014)
This study investigates the diet of breeding Black Sparrowhawks (Accipiter melanoleucus) on the Cape Peninsula of South Africa. Macro-remains of prey were collected from below and around the vicinity of nests throughout the breeding seasons of 2012 and 2013. These prey items were then identified down to species where possible through the use of a museum reference collection. In both years 85.9% of the individual remains were those of Columbidae, which corresponds with the only other diet study on Black Sparrowhawks. Redeyed Doves were the most common prey species, accounting for around 35% of the diet’s biomass and 45% of the prey items. Helmeted Guineafowl were also an important component of the diet for certain nests, making up on average 26.4% biomass of the diet. I found very little difference in diet between the different stages of breeding (pre-lay, incubation and nestling), despite the fact that females only contribute significantly during the nestling state and are considerably larger than the males. I also found little difference in the diet composition between pairs which bred either earlier or later in the year, despite productivity being significantly higher for earlier breeding pairs. However, a crude analysis of the overall diet per month revealed increased diet breadth in the early lay months as opposed to the later months. This was a result of fluctuations in the presence of Laughing Doves, Feral Pigeons and Helmeted Guineafowl, probably driven by those species breeding behaviour. Lastly, I also found no difference in the diet composition between pairs with either pure or mixed plumage morph compositions in this polymorphic species. This study provides further evidence to the claim that Black Sparrowhawks on the Cape Peninsula are benefiting from man-altered environments that provide perfect habitat for suitable prey.